2009
DOI: 10.1097/mca.0b013e32831bd875
|View full text |Cite
|
Sign up to set email alerts
|

Comparative predictive value of infarct location, peak CK, and ejection fraction after primary PCI for ST elevation myocardial infarction

Abstract: In patients undergoing primary PCI, location of infarction is an important independent predictor of high peak CK, low LVEF, and increased mortality. LVEF is a strong predictor of 1-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
3
15
1
1
Order By: Relevance
“…The decreased incidence of cardiac death + re-hospitalization for congestive heart failure was the most significant. The prognosis of patients with MI is closely related to the site of MI (23). Generally speaking, AMI located at the anterior wall has a larger infarction area, and yields a higher incidence of complicated left ventricular insufficiency; leading to higher acute or long-term mortality rate than other infarction sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased incidence of cardiac death + re-hospitalization for congestive heart failure was the most significant. The prognosis of patients with MI is closely related to the site of MI (23). Generally speaking, AMI located at the anterior wall has a larger infarction area, and yields a higher incidence of complicated left ventricular insufficiency; leading to higher acute or long-term mortality rate than other infarction sites.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated whether rhBNP has beneficial effects on this site, and determined its therapeutic intensity. Previous studies (23,24) have selected patients with acute anterior MI, who received pPCI treatment as subjects. Although trial design, patient selection and exclusion criteria, occasional rhBNP use and dose, and control drugs differed among these studies, all these results revealed that rhBNP significantly improved left ventricular remodeling and systolic function within postoperative 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prognostic outcome between anterior and inferior wall MI has been extensively investigated. Nienhuis et al 2 showed more favorable short and long-term clinical outcomes for inferior compared to anterior MI. The extent of myocardial damage in acute left anterior descending artery (LAD) occlusion is commonly larger than in either acute right coronary (RCA) or left circumflex (LCX) artery occlusion simply because it perfuses a larger myocardial territory.…”
Section: Introductionmentioning
confidence: 96%
“…Conversely, more recently, it was demonstrated that it is not the amount of myocardial necrosis that leads to worse outcomes, but it is the degree of remodeling and resulting left ventricular dysfunction associated with these large infarcts, which predicts the worse long-term outcomes. [10][11][12][13] Single photon emission computed tomography (SPECT) is a functional imaging study that provides a visual demonstration of regional perfusion of myocardium. The utility of SPECT in risk stratification for CAD has been well established.…”
Section: See Related Article Pp 458-464mentioning
confidence: 99%